The Concept of Gamification to Increase Position Decision Support System based on SAAS Method - Rahardian, Rifky Lana; Anshari, Muhammad; Oka Saputra, Komang (International Journal of Engineering and Emerging Technology, 2017)
Evaluation Process performance do not match reality, and through a very complicated process. As the employees were assessed on one criterion alone but immediately get a promotion. Though these employees are not necessarily superior to the other criteria, the absence of standards or the weight of a definite value in determining the quality of its staff and the absence of a system that can provide an alternative solution to employee performance evaluation for a promotion. There needs to be a system that can facilitate the General Manager in taking decisions raise. If the decision-making process is aided by a computerized decision support system, is expected to subjectivity in decision making can be reduced and can be replaced with the implementation of all criteria for all employees, so expect employees with the ability (other considerations) the best are selected. By applying the concept of gamification is expected the decision support process becomes more attractive and employees become more motivated in their work.